Co‐administration of kla‐TAT peptide and iRGD to enhance the permeability on A549 3D multiple sphere cells and accumulation on xenograft mice. (18th May 2018) - Hu, Cuihua; Chen, Xiaolong; Huang, Yibing; Chen, Yuxin
Abstract: To enhance the anticancer activity, tumor penetration ability of the hybrid anticancer peptide, in this study, a TAT (RKKRRQRRR) peptide modified kla peptide (KLAKLAKKLAKLAK, with all D‐amino acids), named kla‐TAT, was co‐administrated with the homing/penetrating peptide iRGD which could enhance the permeability of chemical drug in solid tumor and tumor vessel by co‐administration. In this study, the nonsmall cell lung cancer A549 cell line with the iRGD targeting receptor neuropilin‐1 high expression was selected to establish the 2D monolayer cell, 3D multiple cell spheroids, and xenograft mice model. The co‐administration of iRGD strengthened the permeability of kla‐TAT peptide against A549 2D and 3D sphere model with the penetration improvement property of iRGD; more importantly, co‐administration with iRGD dramatically enhanced the accumulation of kla‐TAT peptide in tumor tissue on the xenograft mice model with the homing property of iRGD. The co‐administration of iRGD strategy confers targeting ability to the hybrid peptide kla‐TAT. We believe the chemical conjugation plus co‐administration approach may provide a promising way for cancer treatment in clinical practices. Abstract : The co‐administration of iRGD strengthened the permeability of kla‐TAT peptide against A549 2D monolayer cell model and 3D multiple sphere cell model as well as dramatically enhanced the accumulation of kla‐TAT peptide in tumor tissue on the A549 xenograft mice model.